2011
DOI: 10.1111/j.1460-6984.2011.00073.x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of semantic therapy for word‐finding difficulties in pupils with persistent language impairments: a randomized control trial

Abstract: Four hours of semantic therapy on discrete semantic categories led to significant gains on a general standardized test of word finding, enabling the participants to begin to close the gap between their performance and that of their typically developing peers. These gains were maintained after 5 months. A small amount of therapy can lead to significant gains even with secondary aged pupils with severe language difficulties. However, further studies are needed to find ways of improving word-finding abilities in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
104
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(115 citation statements)
references
References 43 publications
8
104
1
1
Order By: Relevance
“…However, this research is not directly comparable, as it focussed on a broader range of lexical disorders; including receptive as well as expressive vocabulary difficulties. To date, the largest study to focus specifically on children with word-finding difficulties included 15 children (Ebbels et al, 2012).…”
Section: Intervention Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…However, this research is not directly comparable, as it focussed on a broader range of lexical disorders; including receptive as well as expressive vocabulary difficulties. To date, the largest study to focus specifically on children with word-finding difficulties included 15 children (Ebbels et al, 2012).…”
Section: Intervention Studiesmentioning
confidence: 99%
“…Wing, 1990, 6-7 years;Hyde Wright et al, 1993, 8-14 years) and the effect of intervention for WFD can be maintained (Bragard et al, 2012;German, 2002;McGregor, 1994). Ebbels et al (2012) employed an RCT to investigate the effectiveness of a semantic therapy for adolescents with WFDs occurring in the context of severe DLD. Activities included picture-sorting, discussion and comparison of semantic attributes.…”
Section: Intervention Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, studies using standardised tests as outcome measures fail to show significant effects of intervention for these children (Boyle et al, 2009, Gillam et al, 2008, a finding which likely reflects the design and psychometric properties of the tests used (Dockrell and Marshall, 2015). In contrast to this, studies using more tailored measures of progress have found significant gains with intervention targeting either a range of areas (Ebbels et al, in press) or the specific language areas of receptive vocabulary (Parsons et al, 2005, Throneburg et al, 2000, word finding (Ebbels et al, 2012, Hyde-Wright et al, 1993, production and comprehension of specific grammatical structures (e.g., Ebbels et al, 2014Ebbels et al, , 2007, and narrative (Hayward and Schneider, 2000) There is also emerging evidence that children with severe, complex and pervasive communication and language disorders (including those associated with autism and learning disabilities) can make progress with direct individualised intervention, usually in combination with collaborative work (discussed further below). Relevant studies tend to focus on the acquisition of specific skills, e.g.…”
Section: Direct Individualised Intervention (Tier 3b)mentioning
confidence: 99%